2009
DOI: 10.1093/jxb/erp184
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a high-affinity K+ transporter gene PutHKT2;1 from Puccinellia tenuiflora and its functional comparison with OsHKT2;1 from rice in yeast and Arabidopsis

Abstract: A high-affinity K+ transporter PutHKT2;1 cDNA was isolated from the salt-tolerant plant Puccinellia tenuiflora. Expression of PutHKT2;1 was induced by both 300 mM NaCl and K+-starvation stress in roots, but only slightly regulated by those stresses in shoots. PutHKT2;1 transcript levels in 300 mM NaCl were doubled by the depletion of potassium. Yeast transformed with PutHKT2;1, like those transformed with PhaHKT2;1 from salt-tolerant reed plants (Phragmites australis), (i) were able to take up K+ in low K+ con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…HKT transporter genes have also been identified in crop plants, such as wheat and the wheat-relative Triticum monococcum and have similar functions as those in Arabidopsis (Munns et al 2012). Other types of HKT family members, such as TaHKT2;1 from Triticum aestivum, TsHKT1;2 from Thellungiella salsuginea, and EcHKT1;2 from Eucalyptus camaldulensis, also participate in K + transport to maintain K + /Na + balance under salt stress (Ali et al 2012;Ardie et al 2009;Laurie et al 2002;Liu et al 2001;Schachtman and Schroeder 1994). Shkolnik-Inbar et al reported that ABI4 reduced the expression of AtHKT1 to further affect salt tolerance.…”
Section: Aba and Maintenance Of Ion Homeostasis Under Drought And Salmentioning
confidence: 99%
“…HKT transporter genes have also been identified in crop plants, such as wheat and the wheat-relative Triticum monococcum and have similar functions as those in Arabidopsis (Munns et al 2012). Other types of HKT family members, such as TaHKT2;1 from Triticum aestivum, TsHKT1;2 from Thellungiella salsuginea, and EcHKT1;2 from Eucalyptus camaldulensis, also participate in K + transport to maintain K + /Na + balance under salt stress (Ali et al 2012;Ardie et al 2009;Laurie et al 2002;Liu et al 2001;Schachtman and Schroeder 1994). Shkolnik-Inbar et al reported that ABI4 reduced the expression of AtHKT1 to further affect salt tolerance.…”
Section: Aba and Maintenance Of Ion Homeostasis Under Drought And Salmentioning
confidence: 99%
“…and K ? (in heterologous systems) and active at the plasma membrane of root peripheral layers [14,136] are strongly upregulated at the transcriptional level in response to K ? starvation.…”
Section: Epmentioning
confidence: 99%
“…uptake in planta, at least in conditions of high external Na ? [136]. In rice, OsHKT2;1 has been demonstrated to be involved in nutritional Na ?…”
Section: Epmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ionresponsive antiporter/channel genes have been reported in monocot halophyte Puccinellia tenuifl ora ; PutPMP3 -1, and PutPMP3 -2 encoding plasma membrane protein 3 family prevent the accumulation of excess Na + and K + ions (Zhang et al 2008a ). Similarly, PutHKT2 -1 encoding a high-affi nity K + transporter facilitates K + uptake to maintain a high ratio of K + /Na + in the cells (Ardie et al 2009 ). K + is an essential element in protein synthesis as it binds tRNA to the ribosomes (Blaha et al 2000 ).…”
Section: Understanding Molecular Mechanisms Of Salt Tolerance In Halomentioning
confidence: 99%